2011
DOI: 10.4103/2230-8210.77588
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism presenting as recurrent acute pancreatitis: A case report and review of literature

Abstract: The association between pancreatitis and primary hyperparathyroidism (PHPT) is controversial. We report a 32-year-old man who presented with recurrent episodes of acute pancreatitis. Primary hyperparathyroidism was diagnosed after the fourth episode of pancreatitis. He had no additional risk factors for pancreatitis. Eighteen months after successful parathyroid surgery, there has been no recurrence of abdominal pain and his serum calcium is within the normal range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 8 publications
1
13
0
2
Order By: Relevance
“…PHPT can present as recurrent acute pancreatitis or chronic pancreatitis. [ 20 21 ] Previous data from India report that 12–13% patients with PHPT have pancreatitis. [ 6 7 22 ] In our series, pancreatitis was present in only 3 (4.41%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…PHPT can present as recurrent acute pancreatitis or chronic pancreatitis. [ 20 21 ] Previous data from India report that 12–13% patients with PHPT have pancreatitis. [ 6 7 22 ] In our series, pancreatitis was present in only 3 (4.41%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Como lo hicimos en nuestros pacientes, la identificación preoperatoria del adenoma paratiroideo se realiza con ultrasonido de cuello, tomografía de cuello o gammagrafía con sestamibi, esta última con la ventaja de documentar localizaciones ectópicas 7,8,11,13 . La resección del adenoma está indicada en pacientes con hiperparatiroidismo primario sintomático o en aquellos asintomáticos que cumplan uno o más de los criterios internacionales para tratamiento de pacientes con hiperparatiroidismo primario asintomático: calcio sérico mayor de 1 mg/dl sobre el límite superior normal de calcio, depuración de creatinina menor a 60 ml/min, densidad ósea en la cadera, columna o radio distal más de 2.5 desviaciones estándares por debajo de la densidad pico del hueso (T score menor 2.5), antecedente o riesgo de fractura y edad menor a 50 años 7,11 .…”
Section: Discussionunclassified
“…Los valores de paratohormona se normalizan inmediatamente con la resección del adenoma, pudiéndose corroborar en el transoperatorio. Los síntomas relacionados ceden inmediatamente de su resección 7,11,13 . La resección quirúrgica del adenoma paratiroideo normalizó los valores de calcio sérico y paratohormona en los casos presentados, ninguno de los pacientes presentó en su seguimiento nuevo cuadro de pancreatitis.…”
Section: Discussionunclassified
“…Misgar et al reported the case of a 32-year-old man who was diagnosed to have PHTP during the fourth attack of pancreatitis. But the patient did not have any skeletal manifestations and his postoperative period was uneventful (7). PHPT can be part of MEN, types 1 and 2A.…”
Section: Discussionmentioning
confidence: 99%